Structure of Adverse Events Following Immunisation against Coronavirus Infection (COVID-19) in the Kyrgyz Republic - A. A. Zurdinova; Zh. O. Zhumagulova; A. T. Sharaeva; N. Sultanalieva (Безопасность и риск фармакотерапии)
There is considerable interest worldwide in developing safe and effective vaccines against COVID-19. Pharma-covigilance of adverse events following immunisation (AEFIs) is a key to making informed decisions regarding the global COVID-19 vaccination campaign. In the Kyrgyz Republic, there have been developed a national immunisation information system (IIS) for automated recording of vaccines, vaccinated persons, and AEFIs and a mobile application for AEFI reporting, called Den Sooluk.The aim of the study was to analyse the pattern of AEFIs against COVID-19 in the Kyrgyz Republic.Materials and methods: the study analysed the spontaneous safety reports submitted to the national IIS database through the Den Sooluk mobile application from 29.03.2021 to 25.09.2022.Results: according to the data available by 25.09.2022, the total number of vaccinated people in the country amounted to 2,940,082. At the time, the IIS database included 2111 AEFIs: 1 fatal (and coincidental), 3 severe and 2108 minor ones. AEFIs were more frequent in the young and middle-aged population (81.5%), than in the elderly (18.5%). The following AEFIs were reported: injection site pain (21.25%), fatigue (20.7%), headache (19.8%), body temperature above 38 °C (10.10%), miscellaneous symptoms (5.12%), chills (4.41%), dizziness (4.32%), sore throat (3.36%), myalgia (2.9%), and nausea (2.2%).Conclusions: all COVID-19 vaccines used in the Kyrgyz Republic can be considered adequately safe. Pharmacovigilance of AEFIs is an integral part of the requirements to ensure the safe use of vaccines, and collecting of spontaneous reports on AEFIs supports adequate functioning of the post-marketing surveillance system. It is essential to provide access to electronic information platforms to health professionals and patients in order to ensure vaccination transparency and coordination and enable quick and safe reporting of AEFIs associated with the use of COVID-19 vaccines.